Odpowiedzi

2010-03-29T20:32:31+02:00
A) ½x - ¾[x-(4x+1)] = 1- x+1/4
1/2x - 3/4 (x - 4x - 1) = 1 - x + 1/4
1/2x - 3/4 (-3x - 1) = 1 - x + 1/4
1/2x + 9/4x + 3/4 = 1 - x + 1/4
2/4x + 9/4x + x = 1 + 1/4 - 3/4
2/4x + 9/4x + 4/4x = 4/4 + 1/4 - 3/4
15/4x = 2/4 /: 15/4
x = 2/4 x 4/15
x = 8/60
x = 2/15


b) ⅔(3x-1)-3/2[2x+3(x-2)]=1
6/3x - 2/3 - 3/2 (2x + 3x - 6) = 1
2x - 2/3 - 6/2x - 9/2x + 18/2 = 1
4/2x - 6/2x - 9/2x = 1 + 2/3 - 18/2
-11/2x = 6/6 + 4/6 - 54/6
-11/2x = -44/6 /:(-11/2)
x = (-44/6) x (- 2/11)
x = 88/66
x = 8/6
x = 1 i 1/3